Interventions to Improve the Cast Removal Experience for Children and Their Families: A Scoping Review - Pramila Maharjan; Dustin Murdock; Nicholas Tielemans; Nancy Goodall; Beverley Temple; Nicole Askin; Kristy Wittmeier (MDPI AG, 2021)
Background: Cast removal can be a distressing experience for a child. This scoping review aims to provide a comprehensive review of interventions designed to reduce anxiety and improve the child's and family's experience of pediatric cast removal. Methods: A scoping review was conducted (Medline, Embase, PsycINFO, CINAHL, Scopus, grey literature sources). Inclusion criteria: studies published January 1975-October 2019 with a primary focus on pediatric patients undergoing cast removal/cast room procedures. Screening, full text review, data extraction, and quality appraisal were conducted in duplicate. Results: 974 unique articles and 1 video were screened. Nine articles (eight unique studies) with a total of 763 participants were included. Interventions included the following, alone or in combination: noise reduction, electronic device use, preparatory information, music therapy, play therapy, and child life specialist-directed intervention. Heart rate was used as a primary (88%) or secondary (12%) outcome measure across studies. Each study reported some positive effect of the intervention, however effects varied by age, outcome measure, and measurement timing. Studies scored low on outcome measure validity and blinding as assessed by the Joanna Briggs Institute Critical Appraisal Checklist for Randomized Controlled Trials. Conclusion: Various methods have been tested to improve the pediatric cast removal experience. Results are promising, however the variation in observed effectiveness suggests a need for the use of consistent and valid outcome measures. In addition, future research and quality improvement projects should evaluate interventions that are tailored to a child's age and child/family preference.